Neurofibromatosis tipo 1. Más allá de las manchas café con leche: ¿es necesario actualizar criterios? - Vera G, Valentina; Jahr A, Catalina; Vuskovic R, Dinko; Aranibar D, Ligia (Revista Hospital Clínico Universidad de Chile, 2022)
Neurofibromatosis type 1 (NF1) is the most common neurocutaneous syndrome. Diagnosis is based on clinical findings that meets the criteria developed by the NIH in 1997, which remain highly sensitive and specific in adults, but not in children, in which the manifestations vary with age. In children under 2 years in the pretumoral stage with a negative family history, it would be useful to have additional clinical diagnostic criteria. Genetic testing is not widely available and although café-au-lait spots remain the cardinal and most frequent clinical sign, they cannot make the diagnosis of NF-1 on their own.